A STUDY ON THE IMPACT OF OCCUPATIONAL STRESS ON THE PERFORMANCE OF COLLEGE TEACHERS IN SOUTH INDIA (Journal of Pharmaceutical Negative Results, 2022)
Being a teacher is difficult. There are numerous causes, but there are also ways to help the teacher deal with them.One of the primary factors driving many teachers out of the profession is teacher stress. While teaching has always been stressful, it has become exacerbated by the difficulties that many educators have faced as a result of Covid-19. A whopping 60% of teachers reported being stressed. Due to stress, many educators are considering leaving for the first time or have already left the profession.The purpose of this study is to investigate the factors that bring in stress. A convenient sampling technique was used in this study. A total of 220 teachers were included in the study who belonged to Chennai, Bangalore and Kerela states. A previously validated questionnaire named Brief Job Stress Questionnairewhich was adopted for the study. The results of the study revealthatout of the fiveconstructs – time spent outside of work, self-assessment ability, relationships between teachers, social interaction outside teaching and duties outside teaching, the stress is impacted by duties outside teaching and induces them to feel unproductive. This research examined the impact of various dimensions on the stress level of teachers.Confirmatory factor analysis extracted five factors: “Time spent outside of work,” “Self-assessment of one's ability as a teacher,” “Relationship with other teachers,” “Social interactions outside of teaching,” and “Duties outside of teaching.”Originality/value –This study helps to understand the level of stressencountered by teachers in colleges and to take corrective measures to mitigate the level of stress thereby enhancing the standards of working environment.